Odpowiedzi

2010-03-09T15:56:18+01:00
A) -2abc =-2*4*(-1/2)*(-5)= -2*4*(-0,5)*(-5)=-20
b) -3x[do potęgi 2] = -3*(-1/3)[do potegi 2]=-3*1/9=-1/3
c) 1/2mn =1/2*(-8)*2 1/2=0,5*(-8)*2,5=-10
d) 0,2yz = 0,2*(-5)*(-3,2)=10,24
2010-03-09T15:56:38+01:00
A)-2*4*(-1/2)*(-5)=-20
b)-3*(-1/3)do 2 potegi=3/18
c)1/2*(-8)*2=-8
d)0,2*(-5)*(-3,2)=3,2
2010-03-09T16:00:33+01:00
A) -2abc dla a=4 , b=-1/2 c,=-5
= -2 * 10= -20
b) -3x[do potęgi 2] dla x=-1/3
=-3 * 1/9= -1/3
c) 1/2mn dla m=-8 , n=2 1/2
=-10
d) 0,2yz dla y=-5 , z=-3,2
=3,2